2015
DOI: 10.1021/jp5115042
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally Inelastic Scattering of Quantum-State-Selected ND3with Ar

Abstract: Rotationally inelastic scattering of ND3 with Ar is studied at mean collision energies of 410 and 310 cm -1 . In the experimental component of the study, ND3 molecules are prepared by The differences between He and Ar collision partners are explained by differences in the potential energy surfaces that govern the scattering dynamics.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Ar [17], with full selection of the initial state, including this inversion symmetry, and found excellent agreement with close coupling quantum mechanical (QM) scattering calculations.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Ar [17], with full selection of the initial state, including this inversion symmetry, and found excellent agreement with close coupling quantum mechanical (QM) scattering calculations.…”
Section: Introductionsupporting
confidence: 55%
“…More importantly for our current study, recorded velocity map images contained information on the angular variation of the density of scattered ND3 molecules, and hence could be analysed to obtain differential cross sections. The DCSs were extracted from experimental images using a density-to-flux transformation in the same way as described in our recent work [16,17]. This image analysis used an instrument function generated by a Monte Carlo simulation program [30] We discussed the rotational energy level structure of ND3, nuclear spin effects and selection rules for spectroscopic transitions elsewhere [16].…”
Section: A Experimental Apparatusmentioning
confidence: 99%
“…Measurements of rotationally inelastic, quantumstate resolved, differential cross sections were realized using a hexapole-focused beam of ND 3 molecules colliding with various rare gases (Rg's) or molecular hydrogen. 20,[22][23][24] In these crossed beam scattering experiments, velocity map imaging (VMI) with resonance enhanced multi-photon a) Electronic mail: jloreau@ulb.ac.be b) Electronic mail: A.vanderAvoird@theochem.ru.nl ionization (REMPI) detection is used to obtain state-tostate differential cross sections (DCSs) that can be directly compared to theoretical predictions based on accurate potential energy surfaces and quantum-mechanical scattering calculations. This provides a good check of the quality of the potential energy surface (PES) due to the sensitivity of the DCSs to the interaction potential.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations of inelastic scattering in the NH 3 /ND 3 -He and NH 3 / ND 3 -Ar systems 11,43,44 showed that this approximation gives excellent agreement with a more complete model based on full wave functions for the umbrella vibration-inversion.…”
Section: Scattering Calculationsmentioning
confidence: 75%
“…10,11,44,46 The availability of two totally distinct codes provided an ideal check of the accuracy and convergence of our calculations. We included in the closecoupling channel basis all para rotational levels of NH 3 with j ≤ 6 or E rotational levels of ND 3 with j ≤ 7.…”
Section: Scattering Calculationsmentioning
confidence: 99%